Identification of suitable trait index for selection of heat tolerant wheat (Triticum aestivum) genotypes - C, Narendra M; Roy, Chandan; Kumar, Sudhir; De, Nitish (The Indian Journal of Agricultural Sciences, 2020)
Terminal heat stress is one of the major production constraints in wheat-producing areas of south-east Asia. The selection of genotypes based on grain yield per se is not effective under stress condition. In the present study 30 wheat (Triticum aestivum L.) genotypes were evaluated under normal and heat stress conditions during 2016-17 and 2017-18 to determine the suitable trait index for selection of genotypes under non-stress and heat stress environments and identification of heat tolerant genotypes. The observation was recorded for 13 morphological, biochemical and physiological traits. The index based on seven characters like grain yield, days to heading, biological yield, green fodder yield, dry matter content, catalase and peroxidase was most suitable with the genetic gain of 4856.09% and the genetic advancement of 33.09 in normal condition and the index based on five characters comprising days to heading, biological yield, number of tillers, catalase and peroxidase was most suitable with an expected genetic gain of 20101.32% and genetic advance of 35.09. The genotypes RAJ 3765, BRW 3794, HD 2643, SW 129, DBW 14, SW 160, BRW 3759, BRW 3762 and BRW 3800 were identified as moderately tolerant considering selection index score and heat susceptibility index. These genotypes may be promoted for cultivation under late sown conditions and used as parents for the development of genotypes tolerant to terminal heat stress.